Factors Affecting Dymenorrhea in Adolescents - Rijanto Rijanto; Sukesi Sukesi; Adelya Nur Azizah; Sherly Jeniawaty (Humanistic Network for Science and Technology (HNST), 2022)
Dysmenorrhea is one of the menstrual disorders that can cause physical discomfort for a woman, especially in adolescence. This literature review aims to analyze the factors that influence dysmenorrhea in adolescents. The literature search was conducted on five electronic databases (Garuda, Google Scholar, PubMed, ProQuest, and Science Direct) with a cross-sectional and case-control research design published within the last five years, and published in Indonesian and English. The search results of this review found 17 articles that met the inclusion criteria. Physical activity factor (n=11), fast food consumption factor (n=6), age of menarche factor (n=6), and nutritional status factor (n=4). The results of this review state that physical activity factors, consuming fast food, age of menarche, and nutritional status are factors that influence dysmenorrhea in adolescents. Keyword: dysmenorrhea; factors; adolescents